If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + -60 = 5n + -7 + -2n Reorder the terms: -60 + 6n = 5n + -7 + -2n Reorder the terms: -60 + 6n = -7 + 5n + -2n Combine like terms: 5n + -2n = 3n -60 + 6n = -7 + 3n Solving -60 + 6n = -7 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. -60 + 6n + -3n = -7 + 3n + -3n Combine like terms: 6n + -3n = 3n -60 + 3n = -7 + 3n + -3n Combine like terms: 3n + -3n = 0 -60 + 3n = -7 + 0 -60 + 3n = -7 Add '60' to each side of the equation. -60 + 60 + 3n = -7 + 60 Combine like terms: -60 + 60 = 0 0 + 3n = -7 + 60 3n = -7 + 60 Combine like terms: -7 + 60 = 53 3n = 53 Divide each side by '3'. n = 17.66666667 Simplifying n = 17.66666667
| (2x^2+2)+(x^2-4)-(3x^2+1)= | | 1-2x=-5x-14 | | 3y-2x=-1 | | 3p+2=5+2p | | -8+3(7x-6)=-(-2x+7) | | 10-7x=-18 | | 6k+6=7.1k+34.4 | | 2(3c-1)=6c+1 | | 2x+7-10=3(10x+7)+8 | | 35x+500=55x | | (3x^2+4xy-5y^2)+(6x^2-8xy+6y^2)-(2x^2+6xy+9y^2)= | | (3a^2-2a+4)+(a^2-3a+7)= | | 5x-10=-70 | | 34.1-15.5= | | 8x+15y=20 | | 6.5x+4=5.5x | | 3y-2x=-1+2x | | 9x+4-8x=13 | | f+9=63 | | 12x+14=180 | | 5a+10=3a | | m/3+5=2 | | 69=-6n+9 | | 4(2x-3)=x-12+7k | | x+4+14+19=39 | | 2y+3x+x=840 | | 10+4x=5x+14 | | 13v=78 | | x-6=-5+8 | | 45-c=c+15 | | 45-c=c+30 | | 6(5+8r)-3r=6+3(8-3r) |